PSYCHOLOGICAL EMOTIONAL AND PEDAGOGICAL PRACTICE SUPPORT OF INCLUSIVE PRIMARY EDUCATION FOR CHILDREN WITH DISABILITIES (Conferencea, 2023)
Тhe article presents the methodological justification, structure and content of the model of psychological and pedagogical support for inclusive primary education of children with disabilities, describes the conditions for the implementation of inclusive education for primary school children with disabilities